CRIMINAL LIABILITY FOR CHILD RAPE IN THE LEGISLATION OF THE ADVANCED COUNTRIES OF THE WORLD - Bukalerova, Lyudmila; Skripova, Irina (Revista Inclusiones, 2020)
The comparative legal analysis of the application of the norms on child rape, which caused serious harm to the health of victims with similar norms in the legislation of advanced countries of the world. Determining the most effective ways to enforce clause "b" of Part 4 of Article 131 of the Criminal Code of the Russian Federation not only in Russia, but also in the countries that are parties to the Lanzarote Convention. The General scientific methodological approach was applied within the preparation of the article. While doing the research private scientific methods of knowledge (dialectical, analysis, synthesis, generalization) and special scientific methods (comparative legal, legal and technical) were implemented. Following the positive example of the advanced countries of the world (Germany, France, USA, England, China), Russia needs to strengthen criminal liability for sexual offences, particularly, for rape, leading to serious consequences for a child under 14 years of age. In this regard, it is proposed to improve the Russian criminal legislation. If the proposed changes in the Russian legislation are effective in the area under analysis, there is a great chance that Russia's fruitful cooperation with the Lanzarote Convention control mechanism can result in a significant contribution to other states.